2002
DOI: 10.1152/jn.00152.2002
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Exercise Induces a BDNF-Mediated Mechanism That Promotes Neuroplasticity

Abstract: . Voluntary exercise induces a BDNF-mediated mechanism that promotes neuroplasticity. J Neurophysiol 88: 2187Neurophysiol 88: -2195Neurophysiol 88: , 2002 10.1152/jn.00152.2002. We have investigated potential mechanisms by which exercise can promote changes in neuronal plasticity via modulation of neurotrophins. Rodents were exposed to voluntary wheel running for 3 or 7 days, and their lumbar spinal cord and soleus muscle were assessed for changes in brain-derived neurotrophic factor (BDNF), its signal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
397
2
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 591 publications
(444 citation statements)
references
References 30 publications
18
397
2
8
Order By: Relevance
“…It is possible that exercise elicits a general increase in BDNF content that may act directly on oligodendrocytes to regulate their functions such as myelin production and maintenance. We have previously reported that exercise increases the expression of BDNF in motorneurons, and glial-like cells in the white matter surrounding motoneuron axons (Gomez-Pinilla et al, 2002). In addition, it has been shown that long-term locomotor training upregulates BDNF and TrkB receptor expression in oligodendrocytes in the spinal cord (Skup et al, 2002).…”
Section: Bdnf Can Mediate the Effects Of Exercise On Magmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that exercise elicits a general increase in BDNF content that may act directly on oligodendrocytes to regulate their functions such as myelin production and maintenance. We have previously reported that exercise increases the expression of BDNF in motorneurons, and glial-like cells in the white matter surrounding motoneuron axons (Gomez-Pinilla et al, 2002). In addition, it has been shown that long-term locomotor training upregulates BDNF and TrkB receptor expression in oligodendrocytes in the spinal cord (Skup et al, 2002).…”
Section: Bdnf Can Mediate the Effects Of Exercise On Magmentioning
confidence: 98%
“…For example, physical activity promotes adult neurogenesis (van Praag et al, 1999) and neural healing after CNS injury (Molteni et al, 2004). We have shown that physical activity elevates levels of BDNF in spinal cord areas activated by motor and sensory inputs derived from locomotion (Gomez-Pinilla et al, 2002). In the present studies, we investigated the influence of voluntary exercise on molecular systems responsible for growth inhibition such as MAG.…”
Section: Introductionmentioning
confidence: 94%
“…As the brain can neither synthesize nor store energy reserves, daily diet provides the immediate source of energy to the brain, thereby a means to influence brain function. A diet rich in saturated fat and refined sugar (HF), similar in composition to the average popular diet of most industrialized Western societies, can threaten neuronal plasticity and compromise the capacity of the rodent brain for learning (Greenwood and Winocur, 1996;Winocur and Greenwood, 1999;Molteni et al, 2002). On the other hand, epidemiological studies indicate that exercise can decrease cognitive decay associated to aging (Kramer et al, 1999) and is inherently beneficial for reducing the risk of various diseases (Friedland et al, 2001;Laurin et al, 2001).…”
mentioning
confidence: 99%
“…Neurotrophic factors such as BDNF and GDNF trigger the release of pre-synaptic NRG from nerve terminals 28,29) . Importantly, it is also reported that BDNF and GDNF are stored in vesicles and released with activity, and that NRG controls acetylcholine receptor synthesis at neuromuscular junctions 30,31) .…”
Section: Inactivity-related Changes In Diaphragm Musclementioning
confidence: 99%